All about your skin, hair, and teeth - Bailey, Donna; Ardley, Bridget (Austin, Tex. : Steck-Vaughn Library, 1991)
Describes the functions, characteristics, disorders, and care of skin, teeth, and hair.
Rev. ed. of: Skin, hair, and teeth / Bridget and Neil Ardley. 1988.
Includes index.
Keywords: Skin -- Juvenile literature; Hair -- Juvenile literature; Teeth -- Juvenile literature; Skin; Hair; Teeth